Flexible real-time payment methods for mobile communications - O'MAHONY, DONAL EDWARD (IEEE, 2000)
The method of billing users for mobile telephony is based on systems developed over time for fixed networks. We survey the technology involved, and argue that these systems will become increasingly inadequate for large populations of mobile users where frequent roaming is involved. We present two micropayment schemes which permit a caller to inject a payment stream into the network which allows multiple network operators and value-added service providers to be paid in real time. The methods support dynamic pricing by the association of a pricing contract with the call which specifies the cost for each leg of the call route. The system will alleviate problems of mobile fraud, eliminate the need for interoperator billing agreements, and simplify payment for value-added network services. We discuss the relative merits of the two systems described and the characteristics of the prototype implementation.
PUBLISHED
Keywords: mobile phone payment; micropayment